# Education FAQ

(1x+1y=8) +(3x+5y=15), Can You Solve For Y?
3x + 5y = 15 1x + 1y = 8 (multiply by 3, and subtract from 3x + 5y = 15) 3x + 3y = 24 2y = -9 (divide both sides by 2) y = -9/2 = -4.5 Use the second equation x + y =…

(2 004 + (2 004 * 2 004) + (2 004 * 2 004 * 2 004)) / (2 005 + (2…
I want you to write down the process.Thank you in advance.Hi,here is a bonus,I think the entity who can solve this out is a genius! Really!!I have asked many guys to solve…

(2 Sqrt X) + (3(x+1)^2) — (sqrt 4x + X^2), Can You Help?
(2?x) + 3(x+1) 2 — ((?4x) + x 2 ) = (2?x) + 3(x 2 +2x +1) — ((2?x) + x 2 ) = (2?x) + 3x 2 + 6x + 3 — (2?x) — x 2 =…

(2^2x^5y^-3z^4/4^0x^-2y^-8z^5)^3, Can You Simplify And Evaluate?
Simplify and evaluate 2^2 x^5 y^-3 z^4 / 4^0 x^-2 y^-8 z^5)^3 this will become = (4 x 5-(-2) y -3-(-8) z 4-5 /1) 3 cut 4 from 4 = (x 7 y 5 z -1…

(25b^2)^(1/4) Simplify The Expression!, Can You Help?
The indice rule you need to know here is X^(1/a) = a root X So applied here (25b^2)^(1/4) is the same as 4 root (25b^2) I hope this helps (25b 2 ) 1/4 = ((5b) 2 ) 1/4 = (5b) 2/4 = (5b)…

(3 Times The Square Root Of 6) Divided By (the Square Root Of 2),what…
Not decimal answer which is 5.19 but the simplified answer…. (3?6)/(?2) (3?(2*3))/(?2) Both ?2 from denominator and numerator will cancel out and you will left with 3?3 = 3(3)^1/2 = 3(1.732) = 5.196 >>>answer

(-3, -1), (-2,1) Can You Find The Slope Of A Line Through The Pair…
Find the slope of the line determined by the two points (3,1) and (-2,-2) The formula for slope is: m= y2-y1 / x2-x1 In the question we are given: y2=-1 y1=1 x2=-2 x1=-3…

(3,2) And (10,-5) Find The Slope If It Exists, Of The Line Containing…
The slope of a straight line when two points on the line are given is; Slope = (y2-y1)/(x2-x1) (x1, y1) = (3, 2) (x2, y2) = (10, -5) So, the slope is; slope = (-5 -…

(3x+11)/6 — (3-x)/6i How To Get The Correct Answer?
Help solve thanks barry I think you have written the following equation, if I am not wrong. (3x+11)/6-(3-x)/6=0 by taking the LCM which is 6 (3x+11)-(3-x)/6-=0 unambiguous the brackets 3x+11-3+x/6=0 4x+8/6=0 By taking the four common 4(x+2)/6=0 by dividing 4 with 6…

(3x+5)+(4x+1)=?
Solve this problem 3x+5+4x+1=3x+4x+5+1=7x+6 7x+6 — your answer Open the brackets first. 3x + 5 + 4x + 1 3x + 4x + 5 + 1 7x + 6 the value of x can’t be solved because we don’t know whats the other side of the equation . So the answer is…

(3?5-?11)(4+2?11) How To Simplify This Radical?
Use the distributive property. (3?5 — ?11)(4 + 2?11) = 3?5(4 + 2?11) — ?11(4 + 2?11) = 12?5 + 6?55 — 4?11 — 22 I wouldn’t say this is much simpler.

(-4)(-4) To The -2 Power, Can You Help?
(-4)(-4) -2 = (-4)/(-4) 2 = -4/16 = -1/4 Per the order of operations, the term next to the exponent is evaluated first.

(-4,-1),(-2,-5) Find The Slope Of The Line That Passes Through Each…
The slope of line through two points is; m=(y2-y1)/(x2-x1) let (x1,y1)= (-2,-5) and (x2,y2)=(-4,-1) So, m=(-1+5)/(-4+2) m=4/ -2 m=-2

(400,000-600,000)/600,000 / (16,500-13,500)/13,500?
I need to figure out the answer By simplyfying the about cross-question we will get the following; =-200000/600000/3000/13500 =-.33333/.22222 =-1.5 is the answer.

(5d) For D = 8, Please Can You Help Me?
Please help me I’m a little rusty in my algebra but I believe (5d) when d=8 would be 5xd or 5×8 which is 40. Thank you VERY MUCH !! i SPENT ALL MY WEEKEND TRYING TO FIGURE IT OUT!!

(5x+1)^2=36, Solve The Equation?
Solve the equation? Take the square root and solve for x. (5x+1) = ±6 Let’s do -6 first 5x + 1 = -6 5x = -7 x = -7/5 Now for +6 5x + 1 = 6 5x = 5 x = 1 That’s a bit excessive and…

(5x-1)(3x-2) Use FOIL To Multiply, Can You Please Solve This Problem?…
Please solve this problem (5x — 1)(3x — 2) = 5x(3x — 2) — (3x — 2) 15x 2 — 10x — 3x — 2 = 15x 2 — 13x — 2 (3×2 + 3) — (6x + 4) + (3×2 — 5x)

(-7,5); 3x + Y < -6 How Would You Determine If The Ordered Pair Is…
Try it out. 3(-7) + (5) ?< -6 -21 + 5 ?< -6 -16 < -6 The point (-7, 5) is in the solution set of the given inequality. Is that how it will always work…

(7x^2 — X + 1) — (2x^2-x-3) — (5x^2 +3x -10), Can You Perform The…
Perform the indicated operations For this question u have to group similar to terms…that is add x 2 together and attach x’s together so you’ll get 7x 2 — x + 1 — 2x 2 + x + 3…

(7x^2-x+1)-(2x^2-x-3)-(5x^2+3x-10), Can You Help?
(7x^2-x+1)-(2x^2-x-3)-(5x^2+3x-10) = x 2 (7-2-5) + x(-1-(-1)-3) + (1-(-3)-(-10)) = 0x 2 — 3x + 14 = 14 — 3x.

-(7x+7)=1+4(x+9),how To Solve?
Our question is: -(7x+7)=1+4(x+9) Expanding: -7x-7=1+4x+36 Shifting all the x values on the right hand side and adjectives the other on the left hand side. Hence: -7x-4x=1+36+7 Solving: -11x=44 dividing: -x=44/11 -x=4 multiplying both sides by -1: -1*-x=4*-1 So: x=-4 So our value of x is -4

(7x-5)(9x-3),Can You Tell Me?
Ok…..I have no idea what that is supposed to connote and how those numbers were attained. 7X…7 times an unknown(X) -5 times 9 times X(unknown) minus 3……OK…..’splain that in English please. PS: What is the point? What are you trying to figure?? (7X-5) (9X-3) (7X * 9X) + (7X * -3) -(5…

(8 1/2)2=?
(8 1/2) 2= The solution to your math problem (8 1/2) 2 is 17.First make the mixed number «8 1/2 » in to a fraction which equals 17/2 and after that the 2 outside the bracket cancels out this 2 so merely 17 remains.

(-8x^5)(-4x^9),Can You Help Me?
When two algebraic entities are multiplied their coefficients are added to yield a result, provided that the base is the same entity. In this crust the result would be :- (-8x^5)(-4x^9) => 40x^(5+9) => 40x^14

(-8x^5)(-4x^9),Can You Help?
(-8x^5)(-4x^9) = (-8x 5 )(-4x 9 ) = (-8)(-4)(x 5 .x 9 ) = 32x 5+9 = 32x 14

(9D2-12D+4)y=0, Can You Solve The Following Differentials?
Solve the following differentials The characteristic equation is 9D 2 -12D+4=0 (3D-2) 2 =0 D= 2/3, 2/3 The general solution is y=(c1+c2x)e 2/3 x

(a + B)2 ? A2 + B2. Can You Give A Numerical Example To Illustrate…
This question means that when a sum of two numbers is squared the answer is NOT equal to the other side where both the numbers are squared and next added. Let’s put in a number into this equation:…

(A+B+C)’ = A’B’C’ Using Truth Table?
(A+B+C)’ = A’B’C’ using truth table A B C (A+B+C) (A+B+C)’ A’ B’ C’ A’B’C’ 0 0 0 0 1 1 1 1 1 1 0 0 1 0 0 1 1 0 1 1 0 1 0 0 0 1 0 1 0 1 1 0 0 1 0 0 0 0 1 1 0 1 1 0 0 0 1 1 1 0 1 0 0 0 1 1 1 1 0 0 0 0 0 HOPE THIS HELPS (A+B+C’)(A’+B’+C)= A + B+(A +…

(Compound Annuity) What Is The Accumulated Sum Of Each Of The Following…
If the annuity is an «annuity due,» that is, one with the payment made at the initiation of the period, the accumulated value at the winding up of the final period is A = P((1+i) n -1)(1+i)/i = \$500((1.05) 10 -1)(1.05)/.05 =…

(csc^2(x)) / (cot(x)) = Sec(x)*csc(x)?
I can’t seem to be able to solve this correctly, please help…. (csc^2(x)) / (cot(x)) = Sec(x)*csc(x) Taking disappeared hand side (Cosec^2 x) / (Cot x) ——— (a) Cosec x= 1/ Sin x Cot x= Cos x/ Sin x Put values of Cosec x and…